1996
DOI: 10.1006/bbrc.1996.1181
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV and Anti-HBV Activity and Resistance Profile of 2′,3′-Dideoxy-3′-Thiacytidine (3TC) and Its Arylphosphoramidate Derivative CF 1109

Abstract: A novel membrane-soluble prodrug of the 5-monophosphate derivative of 3TC containing a phenyl group and the methyl ester of L-alanine linked to the phosphorus through a phosphoramidate bond with the primary amino moiety (designated Cf 1109) was prepared. The 3TC prodrug proved less potent an inhibitor of HIV-1 and HIV-2 replication in CEM cell cultures than 3TC, but lost only 20-fold antiviral potency in 2-deoxycytidine kinase-deficient CEM/dCK 0 cells compared with a more than 2,000-fold decrease of activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…However, the emergence of lamivudine-resistant HBV may limit the efficacy of lamivudine monotherapy in some patients. [23][24][25][26][27][28][29][30] To date, YMDD mutant have not been detected in lamivudine-naive patients. In the present study, we attempted to detect YMDD mutant before the development of HBV-DNA breakthrough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the emergence of lamivudine-resistant HBV may limit the efficacy of lamivudine monotherapy in some patients. [23][24][25][26][27][28][29][30] To date, YMDD mutant have not been detected in lamivudine-naive patients. In the present study, we attempted to detect YMDD mutant before the development of HBV-DNA breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22] However, the emergence of lamivudineresistant HBV strains was initially noticed in patients who received orthotopic liver transplantation and immunosuppressive therapy. [23][24][25][26][27][28] Such resistant viruses show a characteristic mutation of the 550th amino acid methionine in the YMDD motif of DNA polymerase to isoleucine (YIDD mutant) or valine (YVDD mutant). Honkoop et al 29 recently showed the emergence of such mutant viruses in 5 of 14 (36%) immunocompetent patients who were treated with lamivudine over 26 weeks.…”
mentioning
confidence: 99%
“…10 The emergence of lamivudine-resistant mutants, however, casts a new challenge for such strategy. [11][12][13][14][15][16][17][18][19][20][21] The resistant viruses were initially noticed in patients under immunosuppressive therapy but were later found in immunocompetent patients. Although such mutants were initially considered replication defective, 22 we have recently shown that acute exacerbations occurred frequently and hepatic decompensation may develop in patients with lamivudine-resistant mutants during long-term lamivudine treatment.…”
mentioning
confidence: 99%
“…12 The methionine at codon 552 was either replaced by an isoleucine (M552I) or a valine (M552V). [13][14][15][16][17] In addition, the M552V mutation was frequently accompanied by a leucine 528-to-methionine (L528M) substitution.…”
mentioning
confidence: 99%
“…Examples of a relatively poor conversion rate by the activating enzyme other than ABC are stavudine (d4T) by thymidine kinase (TK) [7,8], zalcitabine (ddC) by 2 0 -deoxycytidine kinase [9,10], and didanosine (ddI) by 5 0 -nucleotidase [4,5]. Therefore, several attempts have been undertaken to deliver activated (phosphorylated) nucleoside analogues directly into the virusinfected target cells [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. One of these approaches has proven very successful when applied on thymidine analogues such as d4T.…”
Section: Introductionmentioning
confidence: 99%